2013
DOI: 10.21149/spm.v56s1.5169
|View full text |Cite
|
Sign up to set email alerts
|

La magnitud de la inseguridad alimentaria en México: su relación con el estado de nutrición y con factores socioeconómicos

Abstract: Objetivo. Describir la distribución de la inseguridad alimentaria (IA) en México, desde la perspectiva del acceso a la alimentación y consumo, y su relación con diversos factores socioeconómicos y del estado de nutrición. Material y métodos. Se presenta información de la Encuesta Nacional de Salud y Nutrición 2012, de la Encuesta Nacional de Ingreso y Gasto en Hogares 2008, y del Consejo Nacional de Evaluación de la Política de Desarrollo Social. La medición de la inseguridad alimentaria se realizó mediante la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 15 publications
(14 reference statements)
0
18
2
18
Order By: Relevance
“…The ELCSA was adapted from various methodologies, including the one used in the United States (Carlson et al 1999;FAO, 2012;Melgar-Quiñónez and Hackett, 2008;Nord et al 2007;Pérez-Escamilla, 2012;Wehler et al 1992), or in Brazil (Segall-Corrêa et al 2014), among others. Its classification system uses a set of fifteen questions used in surveys around the Latin American and the Caribbean that have been proved to be effective in distinguishing the food secure from the food insecure at the household level (Bezuneh et al 2007;FAO, 2012;Melgar-Quiñonez, 2010;Pérez-Escamilla et al 2009;Shamah-Levy et al 2014;Villagómez-Ornelas et al 2014). The ELCSA questions thus represent universal aspects of the experience of food insecurity, capturing information on food shortage, food quantity and quality of diet to determine household food insecurity status (FAO, 2012).…”
Section: Household Food Insecurity Access Scalementioning
confidence: 99%
“…The ELCSA was adapted from various methodologies, including the one used in the United States (Carlson et al 1999;FAO, 2012;Melgar-Quiñónez and Hackett, 2008;Nord et al 2007;Pérez-Escamilla, 2012;Wehler et al 1992), or in Brazil (Segall-Corrêa et al 2014), among others. Its classification system uses a set of fifteen questions used in surveys around the Latin American and the Caribbean that have been proved to be effective in distinguishing the food secure from the food insecure at the household level (Bezuneh et al 2007;FAO, 2012;Melgar-Quiñonez, 2010;Pérez-Escamilla et al 2009;Shamah-Levy et al 2014;Villagómez-Ornelas et al 2014). The ELCSA questions thus represent universal aspects of the experience of food insecurity, capturing information on food shortage, food quantity and quality of diet to determine household food insecurity status (FAO, 2012).…”
Section: Household Food Insecurity Access Scalementioning
confidence: 99%
“…Mexico is a fertile field for strategies against FI, since the severity of FI in the country is increased by many factors such as poverty, marginalization, indigenous languages, average household size, existence of extended households, educational level of the household heads, monthly income and variety of foods in the family diet [6,7,12]. Likewise, rural areas are at a high risk because a higher incidence and level (moderate to severe) of FI is present [6,7,13].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Encuesta Nacional de Salud y Nutrición (ENSANUT) [14] reported that 80% of the households in the rural stratum in Mexico were classified at some level of FI, compared to 67% in the urban area. Children under the age of 12 are the most vulnerable group; in fact, the degree of food insecurity is directly related to the degree of malnutrition in Mexican children as households with moderate food insecurity have a higher prevalence of low height and emaciation [12].…”
Section: Introductionmentioning
confidence: 99%
“…This scale can be used to assess the FI level in households and detect changes in the quality and quantity of food consumed, taking into account the resources available to each household in the past three months (FAO, 2012). Several studies were conducted to validate this new instrument in a number of countries in this region, including Guatemala , Haiti (Pérez-Escamilla et al, 2009), Mexico (Melgar et al, 2005Shamah-Levy et al, 2014;Villagómez-Ornelas et al, 2014), Dominican Republic (Bezuneh et al, 2007) and other countries.…”
Section: Introductionmentioning
confidence: 99%